Electrocardiographic QT Intervals in Infants Exposed to Hydroxychloroquine Throughout Gestation. (October 2020) - Friedman, Deborah M.; Kim, Mimi; Costedoat-Chalumeau, Nathalie; Clancy, Robert; Copel, Joshua; Phoon, Colin K.; Cuneo, Bettina F.; Cohen, Rebecca; Masson, Mala; Wainwright, Benjamin J.; Zahr, Noel; Saxena, Amit; et al.
Abstract : Background: Based on inhibition of viral replication and limited reports on clinical efficacy, hydroxychloroquine is being considered as prophylaxis and treatment of coronavirus disease-19 (COVID-19). Although hydroxychloroquine is generally considered safe during pregnancy based on studies in patients with systemic lupus erythematosus and other rheumatic conditions, there may still be reluctance to institute this antimalarial during pregnancy for the sole purpose of antiviral therapy. Methods: To provide data regarding any potential fetal/neonatal cardiotoxicity, we leveraged a unique opportunity in which neonatal ECGs and hydroxychloroquine blood levels were available in a recently completed study evaluating the efficacy of hydroxychloroquine 400 mg daily to prevent the recurrence of congenital heart block associated with anti-SSA/Ro (anti-Sjögren's Syndrome A/Ro) antibodies. Results: Forty-five ECGs were available for corrected QT interval (QTc) measurement, and levels of hydroxychloroquine were assessed during each trimester of pregnancy and in the cord blood, providing unambiguous assurance of drug exposure. Overall, there was no correlation between cord blood levels of hydroxychloroquine and the neonatal QTc ( R =0.02, P =0.86) or the mean of hydroxychloroquine values obtained throughout each individual pregnancy and the QTc ( R =0.04, P =0.80). In total 5 (11% [95% CI, 4%–24%]) neonates had prolongation of the QTc >2 SD above historical healthy controls (2 markedly and 3 marginally) but ECGs were otherwise normal. Conclusions: In aggregate, these data provide reassurances that the maternal use of hydroxychloroquine is associated with a low incidence of infant QTc prolongation. However, if included in clinical COVID-19 studies, early postnatal ECGs should be considered. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01379573.